Memorandum of Understanding between Daffodil International University and Brac University (2011) - Brac University; Daffodil International University (Brac University and Daffodil International University, 2019)
The agreement made between Daffodil International University and Brac university for implementation of an Integrated Library System (lLS) using KOHA at Daffodil International University Library.